Beyond structural domains: the emerging roles of PDLIM2 in cellular signaling and cancer progression - Shi, Yulian; Fan, Tingyu; Yang, Yuchao; Liu, Jiaxuan; Ouyang, Jun; Dai, Jingxing (Frontiers in Physiology, 2025)
The cytoskeleton not only provides structural support for cells but also plays a crucial role in intracellular information transmission. Cytoskeleton-associated proteins are intricately involved in, and indispensable for, regulating cytoskeletal dynamics. PDLIM2, also known as mystique or SLIM, is localized in the nucleus and cytoplasm and functions as a cytoskeleton-associated protein that facilitates binding of other proteins to the cytoskeleton. PDLIM2 exhibits widespread expression in various tissues and cell types, contributing to cellular proliferation and differentiation processes. This review provides a concise overview of PDLIM2, including its genetic background, structural features, involvement in tumorigenesis and development, as well as potential molecular signaling pathways. Lastly, we address the current limitations in PDLIM2 research while highlighting future prospects.